The Effect of an Electronic Learning Environment According to the Electronic Cooperative Learning Strategy on Cognitive Achievement by Studying Teaching Methods for Students - Alia Hussein Obaid; Nabaa Abdul Amir Abdul Hadi (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to know the effect of an electronic learning environment according to the collaborativee-learning strategy on cognitive achievement by studying teaching methods for female students. Theexperimental approach was used in the study, by two experimental groups, a control, and each group (20)students. To achieve the objectives of the study, the cognitive achievement test was built to study teachingmethods and design an electronic learning environment to study the teaching method material, and theresults indicated that there are statistically significant differences between the averages of the two groups inthe measure of cognitive achievement in the post-application and for the benefit of the experimental group.The results were discussed in light of the theoretical framework, as well as Some recommendations andfuture studies have been drawn up.